IMPLEMENTATION OF THE NATIONAL NARCOTICS AGENCY (BNN) OF TEBING TINGGI CITYIN HANDLING NARCOTICS CASES IN TEBING TINGGI CITY BASED ON TEBING TINGGI CITY REGIONAL REGULATION NUMBER 05 OF 2019 FROM THE PERSPECTIVE OF FIQH SIYASAH DUSTURIYAH - Ridho Khairi Yusri; Zaid Alfauza Marpaung (Journal Analytica Islamica, 2025)
Etymologically, drugs or narcotics come from the English word narcose or narcosis which means to put to sleep and anesthesia. What is meant by Narcotics in Law No. 35 of 2009 is a substance or drug derived from plants or non-plants, both synthetic and semi-synthetic, which can cause a decrease or change in consciousness, loss of feeling, reduce to eliminate pain, and can cause dependence. From data obtained from Tebing Tinggi City Prison, there is an interesting trend in the number of drug cases during the last 5 months at the end of the year and the beginning of 2024. It can be seen that the number of inmates and detainees tends to vary every month. In January, the number of inmates was recorded at 995 people and the number of detainees was 232 people. However, in February, although the number of inmates was the same as the previous month (995 people), the number of detainees increased significantly to 263 people. Then, there was an increase in the number of prisoners in September (1027 people), but the number of detainees remained relatively stable (222 people) The approach used in this study is a qualitative approach, namely data in the form of descriptions of words or attachments to be collected and then analyzed descriptively. Descriptive qualitative research is a study that describes situations and events (Nurdiansyah and Rugoyah 2021) As an institution that has the main task of Preventing the Eradication of Narcotics Abuse and Illicit Trafficking in Tebing Tinggi City, the Tebing Tinggi City National Narcotics Agency must be able to provide guarantees to every community to carry out the duties and functions of the Tebing Tinggi City BNN as regulated by law. Combating illicit trafficking and abuse of narcotics can be achieved through various government strategies and policies which are then implemented comprehensively and simultaneously by relevant officials in collaboration with anti-drug community components. The strategies for combating illicit drug trafficking and abuse include Demand Reduction, Supply Control, and Harm Reduction. Essentially, drug abuse has reached all levels of society. It begins with curiosity, then trial, and then addiction, leading to repeated attempts. This is where the role of the Tebing Tinggi City National Narcotics Agency (BNN) is crucial, along with the Prevention, Eradication, and Eradication of Narcotics Abuse and Illicit Trafficking (P4GN). In this effort, the BNN conducts outreach to various levels of society, especially children and students, as early prevention is essential for them to grow into intelligent future generations.